Studies on Serum LDL-Cholesterol in Second and Third Trimester of Pregnancy - Husain, F; Latif, SA; Uddin, MM (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(3):330-4. The abstract of this article is available on the PubMed website